Measurement of inclusive J/ψ pair production cross section in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; López, Jorge; et al. (Physical review, 2023)
The production cross section of inclusive J/ψ pairs in pp collisions at a center-of-mass energy √s=13 TeV is measured with ALICE. The measurement is performed for J/ψ in the rapidity interval 2.5<y<4.0 and for transverse momentum pT>0. The production cross section of inclusive J/ψ pairs is reported to be 10.3±2.3(stat.)±1.3(syst.) nb in this kinematic interval. The contribution from nonprompt J/ψ (i.e., originated from beauty-hadron decays) to the inclusive sample is evaluated. The effective double-parton scattering cross section is computed, neglecting the single-parton scattering contribution.